Bipolar Verdazyl Radicals for Symmetrical Batteries: Properties and Stability in All States of Charge. Issue 4 (24th November 2022) - Steen, Jelte S.; de Vries, Folkert; Hjelm, Johan; Otten, Edwin
Abstract: Redox flow batteries based on organic electrolytes are promising energy storage devices, but stable long‐term cycling is often difficult to achieve. Bipolar organic charge‐storage materials allow the construction of symmetrical flow batteries (i. e., with identical electrolyte composition on both sides), which is a strategy to mitigate crossover‐induced degradation. One such class of bipolar compounds are verdazyl radicals, but little is known on their stability/reactivity either as the neutral radical, or in the charged states. Here, we study the chemical properties of a Kuhn‐type verdazyl radical (1 ) and the oxidized/reduced form (1 +/− ). Chemical synthesis of the three redox‐states provides spectroscopic characterization data, which are used as reference for evaluating the composition of the electrolyte solutions of an H‐cell battery during/after cycling. Our data suggest that, rather than the charged states, the decomposition of the parent verdazyl radical is responsible for capacity fade. Kinetic experiments and DFT calculations provide insight in the decomposition mechanism, which is shown to occur by bimolecular disproportionation to form two closed‐shell products (leuco‐verdazyl 1H and triazole derivative 2 ). Abstract : Bipolar organic radicals are promising materials for symmetrical redox‐flow batteries. The authors investigate the chemical stability issues that contribute to capacity fade. It is shown that rather than the energized (charged) states, the capacity fade is determined by bimolecular decomposition of the neutral radical.